2018
DOI: 10.7716/aem.v7i4.883
|View full text |Cite
|
Sign up to set email alerts
|

New Compact Microstrip Filters Based on Quasi Fractal Resonator

Abstract: This paper presents new microstrip devices  as single band bandpass and multi band bandstop filters. The proposed filters use  slotted patch microstrip resonator based on quasi fractal geometry, simulated by AWR12 software package. Both filters have quasi elliptic frequency response, designed at centre frequency of  2.437 GHz for bandpass filter and at band frequencies of  2.434, 4.032, 4.976 and 5.638 GHz GHz respectively, for multi bandstop filter. All filters are employed using RT/Duroid 6010.8 LM substrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…The end output is shown in Figure 15 when a moderately detailed image is used as input. Image filtering by convolution can be adopted along with wireless communication elements as in [10][11][12][13][14], for better wireless transmission of images.…”
Section: Resultsmentioning
confidence: 99%
“…The end output is shown in Figure 15 when a moderately detailed image is used as input. Image filtering by convolution can be adopted along with wireless communication elements as in [10][11][12][13][14], for better wireless transmission of images.…”
Section: Resultsmentioning
confidence: 99%
“…Among the reported resonator structures such as star-shaped ring (Wei and Kewei, 2012), square patch (Yeh et al , 2014; Mezaal et al , 2018; Liu et al , 2019; Cheng et al , 2019; Zhao et al , 2020), octagonal patch (Karthie and Salivahanan, 2019), star-shaped loop (Avinash and Rao, 2017) and hexagonal loop (Song et al , 2017) with different patch/slot as perturbation elements, the proposed square patch resonator with a diagonal square perturbation patch exhibits a compact size of 7.35 × 7.35 mm 2 and a size reduction of 61%, respectively. Amid the filter designs fabricated on RT/duroid 6010 substrate with a relative permittivity of 10.2, the proposed structure offers more miniaturization on the same substrate in addition to the filter designs by Wei and Kewei (2012), Liu et al (2019) and Cheng et al (2019) on different substrates.…”
Section: Fabrication and Measurementmentioning
confidence: 99%
“…In the design of BPFs, different slotted perturbations such as cross-slots (Zhu et al , 2005), diagonal slot (Liu et al , 2019), CSRR slot (Cheng et al , 2019) and corner slots (Zhao et al , 2020) were used to reduce the size and radiation loss of dual-mode patch resonators. Meanwhile, with the diagonal square patch as a perturbation element, dual-mode patch resonators by Yeh et al (2014) and Mezaal et al (2018) were reported on a square patch having size reductions of 14.1 and 50%. Several other resonator structures with perturbation elements such as a star-shaped ring with a trapezoidal patch (Wei and Kewei, 2012), hexagonal loop with corner patch (Song et al , 2017) and octagonal fractal patch with a square patch (Karthie and Salivahanan, 2019) were also demonstrated with size reductions of 37, 46.6 and 22%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Microstrip technology has been widely adopted in many RF and microwave devices in numerous wireless applications due to its cost effectiveness, smallness and desired frequency responses. Microstrip devices may include microstrip filters [1][2][3][4][5][6][7], microstrip diplexers [8,9] and microstrip antennas [10][11][12][13][14][15]. In recent years, specifically, bandpass filters (BPFs) have a significant role in modern wireless mobile communication systems.…”
Section: Introductionmentioning
confidence: 99%